LncRNA XIST functions as a molecular sponge of miR‐194‐5p to regulate MAPK1 expression in hepatocellular carcinoma cell - Kong, Qinglei; Zhang, Shaoquan; Liang, Caiqian; Zhang, Ying; Kong, Qingcong; Chen, Shuxian; Qin, Jie; Jin, Yi (Journal of cellular biochemistry, 2018)
Increasing evidence highlights the important role of XIST, a long non‐coding RNA (lncRNA), in the regulation of multiple cancers. However, the underlying mechanism of XIST in human hepatocellular carcinoma (HCC) still remains to be explored. Herein, intended to investigate the functional role of XIST in HCC initiation and progression. We first detected that XIST was significantly upregulated in HCC tissues and associated with tumor size and vascular invasion. Gain‐ and loss‐of‐function of XIST further presented that XIST promoted the progression of HCC cells, including proliferation, migration, and invasion. Moreover, silencing of XIST could inhibit tumor growth in vivo. We also found that XIST could target miR‐194‐5p and thus decrease miR‐194‐5p expression. Besides that, restoring XIST could reverse the inhibitory effect of miR‐194‐5p on the proliferation and invasion of HCC cells. We further elucidated such rescue role might through derepressing MAPK1 expression, the target of miR‐194‐5p. In brief, the above results elucidate the important role of XIST in HCC tumorigenesis, suggesting that XIST might be a candidate prognostic biomarker and a novel therapeutic target for treating HCC. We found that XIST was significantly upregulated in HCC tissues and associated with tumor size and vascular invasion. Gain‐ and loss‐of‐function of XIST revealed further presented that XIST promoted the malignancy of HCC cells, including proliferation, migration, and invasion. We also found that XIST could target miR‐194‐5p and thus decrease miR‐194‐5p expression.